Affect, Disordered Eating Attitudes and Behaviors, and Orthorexia Nervosa Among Women: Mediation Through Intuitive Eating - Mehri Khoshzad; Christophe Maïano; Alexandre J. S. Morin; Annie Aimé (Behavioral Sciences)
Intuitive eating is an adaptive eating style that could help explain part of the relation between affect and eating behaviors. However, research in this area remains limited. The objectives of this study are twofold. First, we examine the relation between affect, disordered eating attitudes and behaviors (DEABs), and orthorexia nervosa (ON). Second, we investigate the mediating role of intuitive eating regarding these relations. A sample of 197 French-speaking Canadian women, aged from 18 to 69, participated in the study. The results showed that negative affect was related to DEABs and ON, but not positive affect. Statistically significant associations were also found between affect (negative and positive) and the four dimensions of intuitive eating. Additionally, negative relations were found between intuitive eating dimensions and most types of eating behaviors (encompassing DEABs and ON), except for dieting. Finally, our results revealed that the relations between affect (positive and negative) and most types of eating behaviors were indirect (i.e., suggesting mediation) via intuitive eating. Based on these results, it seems that interventions addressing affect regulation and eating behaviors could benefit from including a focus on intuitive eating.